PRODUKSI ASAM GAMMA AMINOBUTIRAT (GABA) LACTOBACILLUS PLANTARUM PH715 PADA SUSU TERFERMENTASI - Ni Wayan Nursini; Ida Bagus Agung Yogeswara (ARGIPA (Arsip Gizi dan Pangan), 2023)
Fermentation has a great potential to increase gamma amynobutiric acid (GABA) content, one of which is fermented milk. In particular, fermentation by lactic acid bacteria can produce GABA in its most natural and suitable form. The purpose of this study was to examine the potential of Lactobacillus plantarum PH715 to produce GABA as a starter for fermented milk. Temperature and incubation time are factors that affect the production of GABA in fermented milk. The pH measurement with pH meter, population with scatter method, GABA content produced was analysed quantitatively using UPLC. Based on the observation, L. plantarum PH715 is a gram-positive bacteria, bacil-shaped, purple in colour, catalase negative and does not produce gas. The pH value at the fermentation time of 48 hours with a temperature of 37°C and 43°C has met the pH requirements as fermented milk, which are 4.21 and 4.25. The population of L. plantarum PH715 at incubation times of 0, 12, 24, 36 and 48 hours at temperatures of 37°C and 43 °C met the probiotic requirements. The highest GABA content of fermented milk by L. plantarum PH715 was at an incubation temperature of 37°C for 48 hours with the addition of 2% MSG at 2.09mg/mL.